PENINGKATAN KEMAMPUAN MEMBACA MEMINDAI MELALUI PENDEKATAN COOPERATIVE LEARNING TIPE JIGSAW II DI KELAS V SEKOLAH DASAR NEGERI 08 PADANG BESI KOTA PADANG - refril dani randi eka putra (LPPM Universitas Muhammadiyah Muara Bungo, 2021)
This research starts from the reality in the field, namely the scarcity of using approaches in learning and the lack of use of learning resources and tools. This is caused by learning that is still conventional so that students are less interested in participating in learning. For this reason, the authors are interested in improving the process of learning to scan reading in Indonesian language learning through the implementation of Classroom Action Research (CAR) using a Jigsaw II type cooperative learning approach. This Jigsaw II type cooperative learning approach is a learning approach that provides opportunities for students to think and discuss with friends to make themselves